Rachunkowość finansowa i zarządcza w jednostce gospodarczej w aspekcie integracji - Dyduch, Alina; Bek-Gaik, Bogusława (Financial and managerial accounting of enterprises in the aspect of integration, 2008)
In the article the attention is paid to the necessity of the integration of financial and managerial accounting. The aims of these two systems of accounting, their limitations and characteristic features of strategic managerial accounting are indicated. Strategic managerial accounting will be the leading tool in the future on account of usefulness of information managers are provided.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 71-77